2022
DOI: 10.31635/ccschem.022.202101666
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Metal–Organic Frameworks with Unique Oriented Layers for Oxygen Reduction Reaction: Tailoring the Activity through Exposed Crystal Facets

Abstract: As one of the most important family of porous materials, metal-organic frameworks (MOFs) have well-defined atomic structures. This provides ideal models for investigating and understanding the relationships between structures and catalytic activities at a molecular level. However, the active sites on the edges of twodimensional (2D) MOFs have rarely been studied as they are less exposed to the surfaces. Here, for the firsttime, we synthesize and observe that the 2D layers can align perpendicular to the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…The selected area electron diffraction (SAED) pattern (Figure 3d) is matched well with the simulated electron diffraction (ED) pattern of ZIF-L along the [100] zone axis (Figure S1). 30,31 The ultralow-dose high-resolution transmission electron microscopy (HRTEM) image confirmed the high crystallinity of ZIF-L, and no small particles were generated inside (Figure 3c). By applying contrast transfer function (CTF) correction to the cropped HRTEM, it is found that the fine structure of the exposed facet is similar to the (100) facet of ZIF-L, demonstrating that the incorporation of Ni does not affect the crystal structure (Figure 3e, f).…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…The selected area electron diffraction (SAED) pattern (Figure 3d) is matched well with the simulated electron diffraction (ED) pattern of ZIF-L along the [100] zone axis (Figure S1). 30,31 The ultralow-dose high-resolution transmission electron microscopy (HRTEM) image confirmed the high crystallinity of ZIF-L, and no small particles were generated inside (Figure 3c). By applying contrast transfer function (CTF) correction to the cropped HRTEM, it is found that the fine structure of the exposed facet is similar to the (100) facet of ZIF-L, demonstrating that the incorporation of Ni does not affect the crystal structure (Figure 3e, f).…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…17,22 2D leaf-like ZIF-L materials have also been used as a core or self-sacricial template to construct MOF-on-MOF materials. 18,23,24 However, heteroepitaxial growth of a 2D MOF on another 2D MOF still remains challenging. 2D MOFs are normally composed of layered structures, so the interaction between two 2D MOFs is weak, which makes it difficult to achieve heteroepitaxial growth of a 2D MOF on another 2D MOF.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] The ORR occurring at cathode is a fourelectron process and sluggish in kinetics. [12][13][14][15][16] Platinum-based catalysts are still most efficient for ORR in the pass decades. However, high cost and low stability of platinum-based catalysts limit their large-scale applications.…”
Section: Introductionmentioning
confidence: 99%